2015
DOI: 10.1016/j.yrtph.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

New investigations into the genotoxicity of cobalt compounds and their impact on overall assessment of genotoxic risk

Abstract: The genotoxicity of cobalt metal and cobalt compounds has been widely studied. Several publications show induction of chromosomal aberrations, micronuclei or DNA damage in mammalian cells in vitro in the absence of S9. Mixed results were seen in gene mutation studies in bacteria and mammalian cells in vitro, and in chromosomal aberration or micronucleus assays in vivo. To resolve these inconsistencies, new studies were performed with soluble and poorly soluble cobalt compounds according to OECD-recommended pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 52 publications
(71 reference statements)
1
11
0
Order By: Relevance
“…[10][11][12][13][14] More recently, Mitchell, et al showed that bacteria Shewanella oneidensis rapidly developed resistance to nano-NMC aer chronic exposure, indicating the potential effect of NMC on the genetic materials in biological organisms. 15 Such discoveries, along with the fact that nickel and cobalt ions are known to induce genotoxicity, 16,17 indicate that DNA damage is a likely potential toxicity mechanism of nano-NMC in bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] More recently, Mitchell, et al showed that bacteria Shewanella oneidensis rapidly developed resistance to nano-NMC aer chronic exposure, indicating the potential effect of NMC on the genetic materials in biological organisms. 15 Such discoveries, along with the fact that nickel and cobalt ions are known to induce genotoxicity, 16,17 indicate that DNA damage is a likely potential toxicity mechanism of nano-NMC in bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Co 3 O 4 -NPs are intensively used in many biomedical applications including imaging, cancer therapy, and gene therapy (Magaye, Zhao, Bowman, & Ding, 2012). However, the wide application of these MNPs led to their release into the environment in various ways resulting in an increased human exposure to these NPs via inhalation, oral ingestion, and dermal contact (Kirkland et al, 2015). Upon exposure, NPs can penetrate cells more rapidly and provide unprecedented toxicological interactions with cell biomolecules (Jeon, Park, Rhee, & Lee, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Co 2+ plays a quite important role in the human body because it is the central atom of cobalamin, a coenzyme precursor, whose deficiency causes anemia (Paustenbach et al 2013 ). Nevertheless, its genotoxic properties were also discovered, which should be taken into account in the overall Co 2+ assessment (Kirkland et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%